Okra Infusion Water Improving Stress Oxidative and Inflammatory Markers on Hyperglycemic Rats (Bangladesh Journal of Medical Science, 2019)
Objective: Okra has been known for its properties in improving diabetes markers. Most study used okra extract instead of its infusion water. Okra infusion water (OIW) contains polysaccharide and viscous fiber that delay gastric emptying, and help controlling glucose and HbA1C level. As the glucose low level, so does the inflammation and oxidative stress on hyperglycemic rats. This study aims to investigate the effect of OIW in improving glucose level, HbA1C, SOD and CRP levels.Materials and methods: Posttest only control group design was applied to this experimental study using 15 male wistar rats divided randomly into 3 groups: Control, Streptozotocine (STZ), Streptozotocine+okra (OKRA). STZ, and OKRA groups induced with 65 mg/kg BW Streptozotocine and 110 mg/kg BW Nicotinamide on day 8. After the desirable glucose level achieved, OKRA were given 3.6 ml OIW on day 12-28. Data were analyzed using ANOVA in each variable.Results: Fasting and Postprandial Glucose level of OKRA (137,40±3,57 mg/dL and 154.58±2.71 mg/dL), STZ (251,77±2,30 mg/dL and 270.18±3.03 mg/dL); HbA1C level of OKRA (7.93±0.25), STZ (21.29±0.65); SOD level of OKRA (55.292±3.77%), STZ (16.472±5.298%); CRP level of OKRA (1,540±0,059 mg/dL), STZ (2,230±0,093 mg/dL)Conclusions: OIW able to improve glucose, HbA1C, SOD, and CRP level on hyperglycemic rats.Bangladesh Journal of Medical Science Vol.18(4) 2019 p.748-752